Transparency and Pre-meetings - Job Swank; Otto Swank; Bauke Visser (Tinbergen Institute, 2006)
Some committees are made up of experts, persons interested in both the (subject) matter at hand and in coming across as able decision-makers. Such committees would like to conceal disagreement from the public. We present a theory that describes the reaction of experts to the requirement to publish verbatim transcripts of their meetings: the emergence of an informal `premeeting'; the move of the real debate from the formal meeting to the premeeting; and the drop in disagreement in the formal meeting. We analyse what the effect is on accountability and quality of decision-making. Finally, we present evidence suggesting that our model describes the way members of the Federal Open Market Committee in the United States responded to the publication of verbatim transcripts of their meetings.
Keywords: D71; D72; D82; 330; Committees; pre-meetings; reputational concerns; transparency